Analysis of Lead Metal Contents (Pb) in Various Cosmetic Dosage Forms Using the Atomic Absorption Spectrophotometry (AAS) Method - Permatasari, Amelia Dyah; Syifa, Dewi Musnifatus; Zabrina, Leilani; Artanti, Naura; Sari, Novia; Desnita, Syifa (Politeknik Medica Farma Husada Mataram, 2024)
Cosmetics are the preparations whose products are most widely used by people in all circles, from babies to adults. However, it is not uncommon to find dangerous substances contained in cosmetics, one of which is lead contamination, so it is necessary to test the dangerous substances in them. This review aims to provide information regarding the presence and levels of the heavy metal lead in various cosmetic samples using the atomic absorption spectrophotometry method and to analyze the dangers it causes. The method used is a literature review of articles with the keywords